Preventing Child Marriage in Bone District, South Sulawesi: Perspective of Islamic Family Law - Muljan, Muljan; Mustafa, Mustafa; Ilmiati, Ilmiati; Rahmawati, St.; Rosita, Rosita (El-Usrah: Jurnal Hukum Keluarga, 2024)
This research discusses the role of child marriage prevention strategies (SIP-PEKA) in efforts to prevent child marriage in Bone district. The main research problem is the role of SIP-PEKA in efforts to prevent child marriage in Bone Regency. This research uses theoretical legal methods with a maqāṣid al-sharī'ah approach, while the data collection technique is documentation study. The research results show that SIP-PEKA has succeeded in preventing child marriage in Bone Regency, which was carried out using an integrated system with coordination with various parties and across agencies. Although there are obstacles to SIP-PEKA, internal obstacles such as: lack of budget and problems with the cohesiveness of agencies, as well as external obstacles such as: economic problems, culture, children's morals, religious perceptions, and community non-compliance with applicable laws. Meanwhile, evidence of the role of SIP-PEKA in efforts to prevent child marriage in Bone Regency includes: preventing child marriage by providing guidance and counseling, supporting the creation of Village Regulations; limiting marriage dispensations at the Religious Courts, and refusing to register marriages at the KUA. Apart from that, SIP-PEKA also plays an indirect role in the growth of the human development index (HDI) of Bone Regency, because it contributes to reducing the crisis in the health, education and economic sectors of children in Bone Regency. Therefore, the prevention of child marriage carried out by the Bone Regency government is in accordance with maqāṣid al-sharī'ah and is important in the study of Islamic family law.